Exploring the Impact of Women’s Knowledge and Attitude Towards Food Waste Management Practices in Melaka Tengah, Melaka - Mushaireen Musa; Khazainah Khalid; Izzat Zulhilmi Zahirruden; Nurul Syamilah Ismail; Jazira Anuar (Information Management and Business Review, 2025)
Food waste is a significant global issue, and Malaysia is no exception. It has far-reaching negative effects, including higher food production costs, adverse impacts on human health, and environmental degradation. Therefore, this study assesses women's knowledge and attitude towards food waste management in Melaka Tengah, Melaka. An online self-administered questionnaire with a Likert scale was distributed among 384 respondents as part of the study's quantitative methods. The Statistical Package for the Social Sciences (SPSS) Version 26 was used for data analysis. The data analysis methods included reliability, descriptive, and Pearson correlation analyses. The results indicated a positive correlation between knowledge and attitudes toward food waste management practices among women in Melaka Tengah, Melaka. Effective food waste management is essential for building sustainable systems and addressing the interconnected social, economic, and environmental challenges posed by waste.